Pause & effect : the art of interactive narrative - Meadows, Mark Stephen (Voices Ser., 2002)
Interactive narrative is the cornerstone for many forms of digital media: web sites, interface design, gaming environments, and even artificial intelligence. In Pause & Effect, Mark Stephen Meadows examines the intersection of storytelling, visual art, and interactivity. He takes the key principles from these areas and applies them to the design, architecture, and development of successful interactive narrative. This provocative book will appeal to designers with its edgy aesthetic and artistic sensibility. Striking graphic and typographic imagery complement unique design features that encourage interactivity through varying levels of information, different navigational possibilities, and even flip-book animations.